Joint angle, moment and power compensations in dogs with fragmented medial coronoid process - Burton, N. J.; Dobney, J. A.; Owen, M. R.; Colborne, G. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Fragmented medial coronoid process (FMCP) is the most common cause of forelimb lameness in juvenile medium and large breed dogs; however methods of assessing the disruption to their gait remain subjective. The purpose of this study was to objectively quantify the mechanical disruptions to gait in dogs with arthroscopically confirmed unilateral FMCP. Seven dogs underwent full inverse dynamic analysis at the time of diagnosis. Kinematic and force data were collected from both forelimbs at trot. Stance phase joint angles, net joint moments and net joint powers were calculated using custom software. There were gross differences in kinetic and kinematic patterns between FMCP affected and compensating forelimbs. Stance time was 0.24 sec on the lame side and 0.26 sec on the compensating side. The shoulder and the elbow were more flexed at ground contact, and elbow, carpal and MCP joints had smaller ranges of motion on the lame side. Net joint moments were significantly reduced (P<0.05) in the elbow, carpal and MCP joints of the FMCP affected limb. Net joint powers were likewise significantly smaller (P<0.05). However, the overall moment and power patterns persisted. Total limb support moment was significantly smaller on the affected side (P<0.05). Total limb power was significantly reduced on the affected side (P<0.05) being most affected in its propulsive phase in the second half of stance. Inverse dynamic analysis of this clinical condition is an objective means by which to assess the mechanical disruption to gait.
Keywords: Canine elbow dysplasia; gait analysis; biomechanics